A Literature Review: Parental Needs in The Neonatal Intensive Care Room - Sri Hendrawati; Fanny Adistie; Nenden Nur Asriyani Maryam (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Infants’ hospitalization in the neonatal intensive care unit (NICU) adversely affect infants and parents. Many activities have been developed to minimize the negative impact of infants’ hospitalization, one of them is applying the family centered care method. The first step of the method is to identify parent’ needs. This literature review is aimed to identify the needs of parents with critically ill infants in the neonatal intensive care unit. Articles were collected from several databases including Medline, CINAHL, EBSCOhost, Google Scholar, PubMed, and Proquest. The keywords were critically ill infants, family centered care, the needs of parents, and neonatal intensive care unit, qualitative, and quantitative studies. The articles reviewed were only articles with full text, written in English, and published during period 2004 to 2017. The study was criticized by the author using the Critical Appraisal Tool from JBI (Joanna Briggs Institute). 10 articles that related specifically to parental needs were discovered. Needs of parents with critically ill infants, including the needs to (1) have a positive acceptance and caring attitude of nurses towards infant and parents; (2) get an accurate information, effective communication, and parents’ involvement in decision making regarding to the condition of the infant; (3) have confident and believe that infant get the best care; (4) have an adequate contact with infant; (5) have opportunity in caring for the infant with the guidance and supervision of nurses; and (6) obtain comfortable neonatal intensive care unit environment. Each parent has a different priority of their needs. This needs identification would help nurses in integrating parents' need for the family centered care approach. As a result, parents would meet their needs, feel satisfied, and improved the infants’ quality of life.Keywords: Neonatal Intensive Care Unit, Parental Needs